COMPREHENDING ADVERTISEMENTS THROUGH JEAN BAUDRILLARDS POSTMODERNISM - Ekawati Marhaenny Dukut (Soegijapranata Catholic University, 2006)
Nowadays people are living in a postmodern society, which is nihilistic because many things are being simulated that no one actually knows which is real. What people see on television or a magazine, for example, is regarded more real than the reality itself. One of the factors that make a society feel more comfortable in living in a hyper-real world is because of the existence of advertisements or ads. Thus, to understand what is signified by an ad, a reader or consumer needs to take in mind the theory of postmodernism laid out by Jean Baudrillard.